Foreign Direct Investment and Economic Growth of South Asia - Sapkota, Suresh; Gautam, Dilli Raj (The Lumbini Journal of Business and Economics, 2023)
The study aims to investigate the effect of foreign direct investment on the economic growth of four countries in South Asia. The inflow of foreign direct investment, inflation, and public expenditure used as independent variables. Whereas economic growth rate used as a dependent variable. All variables are based in current price and data has been collected from the source of World Bank from the fiscal year 2000 to 2022 A.D. Considering the large amount of public expenditure in the South Asian Countries in 2022 AD, Four countries viz. India, Bangladesh, Pakistan, and Nepal were selected to collect the data. Panel regression has been used for effect analysis. Empirical study shows that there is a positive and statistically significant effect of foreign direct investment on economic growth. However, public expenditure has positive but insignificant effect as well as inflation has a negative and statistically insignificant effect on economic growth.